ANATOMICAL STRUCTURE OF BLACKBERRY AND RASPBERRY FRUITSTALKS IN CONNECTION WITH THE QUALITY OF THE BERRIES - E. A. Dobrenkov; L. G. Semenova; E. L. Dobrenkova (Труды по прикладной ботанике, генетике и селекции)
Presented here are the results of the study of the anatomical structure of fruitstalks in normally developed, underdeveloped and fasciated fruits of blackberry and raspberry. Specific features of the structure of tissues and vascular bundles are shown.